The application of the digital signature laws in governing internet banking security in Malaysia : with special reference to the EU directive and the UK laws on electronic signature / Hartini Saripan - Saripan, Hartini (Institute of Graduate Studies, UiTM, 2012)
Despite the recent trend in other jurisdictions such as the European Union and the State of Utah, USA in investigating into the issue relating to the application of the electronic signature laws, including a digital signature, such concern has never been methodically explored in Malaysia. This study aims at examining the application of the Digital Signature Act 1997 and its 1998 Regulations in governing the security of Internet banking. It underscores the extent to which the said laws were applied by the banks under study and the means in which governance was being exercised. The relationship between the adoption of a digital signature and its laws has somehow informed the application of the latter, which amplifies the debate concerning its under-utilization. A thesis statement of the study is the minimal application of the digital signature laws in securing Internet banking transactions in Malaysia has in turn informed the emergence of other governing modalities including technology, guidelines as soft law instrument, contractual terms and conditions, code of practice and security policy as well as netiquette and norms of Internet banking users.